Critical success factors of the policy plan for the imposition of excise tax on packaged sugar-sweetened beverages in Indonesia based on SWOT analysis - Nurlaeli, Isna (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: To curb the rising consumption of packaged sweetened beverages and mitigate the increasing prevalence of diabetes, the World Health Organization (WHO) recommends the use of fiscal instruments. Inspired by other countries that have successfully imposed excise taxes on sugar-sweetened beverages (SSB), Indonesia, which has the fifth-highest number of diabetes cases globally, plans to implement a similar policy starting in 2023. Methods: This research employs a qualitative approach through literature studies and interviews with two employees from the Directorate General of Customs and Excise (DGCE). A Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis framework is applied to identify the Critical Success Factors (CSFs) of the policy across three key dimensions: policy design, implementation process, and taxation institutions. Findings: The SWOT analysis highlights various internal and external factors influencing policy implementation. Strengths include government commitment and public health concerns, while weaknesses involve potential industry resistance and consumer behavior adaptation. Opportunities lie in increased public awareness and revenue generation, whereas threats include regulatory challenges and economic impacts on related industries. Conclusion: To ensure the successful implementation of SSB excise taxation, this study recommends strategic approaches for the DGCE and relevant ministries/institutions. These include refining policy frameworks, strengthening enforcement mechanisms, enhancing public education on health risks, and fostering collaboration between stakeholders. Novelty/Originality of this article: This research provides a structured analysis of the critical success factors and strategic recommendations for implementing SSB excise taxation in Indonesia, offering insights for policymakers to optimize its effectiveness in reducing sugar consumption and improving public health.